CRISPR/Cas9-mediated miR-21 editing in high-grade urothelial carcinoma cells and its biological effects - Maria Carolina Yi Lin Lee; Juliana Alves Camargo; Giovana Caetano Vilas Boas; Karina Serafim Silva; Luana Pereira Silva; Carolina Mie Mioshi; Ruan Pimenta; Iran Amorim Silva; Katia Ramos Moreira Leite; William Carlos Nahas; Sabrina T dos Reis (Molecular Biology Reports, 2026)
Background Urothelial carcinoma, the predominant form of bladder cancer, represents a global public health challenge due to its high rates of recurrence and progression. At the molecular level, microRNA-21 (miR-21) has been characterized as an “oncomir” because of its ability to negatively regulate tumor suppressor genes, thereby promoting tumor survival and progression. In this context, the CRISPR/Cas9 system has emerged as a precise genome-editing tool. Objective To investigate the biological effects of miR-21 modulation using CRISPR/Cas9-mediated genome editing in the T24 high-grade invasive urothelial carcinoma cell line. Methods The CRISPR/Cas9 system was delivered as a ribonucleoprotein (RNP) complex. Editing efficiency was assessed using quantitative reverse transcription PCR (RT-qPCR). Functional effects were evaluated through gene expression assays, cell migration assays, as well as Matrigel invasion assays. The presence of the Cas9 protein was confirmed by immunofluorescence. Results CRISPR/Cas9 treatment targeting miR-21 showed a trend toward reduced miR-21 expression (p = 0.0563), although this did not reach statistical significance. A statistically significant increase in MASPIN (p < 0.0001) and PDCD4 (p = 0.0239), as well as a trend toward increased PTEN expression (p = 0.055), was observed following treatment. Functionally, a significant reduction in the migratory capacity of edited cells was observed after 48 h (p = 0.0334). The presence of Cas9 was successfully confirmed in transfected cells. Conclusion These findings suggest that CRISPR/Cas9-mediated modulation of miR-21 may influence tumor suppressor pathways and reduce the migratory potential of urothelial carcinoma cells.

Minimum mortality temperature by cause of death and age group: A multi-country observational study (1990–2019) - Seunghyun Eom; Aurelio Tobias; Masahiro Hashizume; Daewon Yang; Claire Demoury; Eric Lavigne; Aleš Urban; Klea Katsouyanni; Francesco Sera; Paul Lester Carlos Chua; Susana das Neves Pereira da Silva; Dominic Royé; et al. (Environmental Research, 2026)

Standardized microhaplotype databases and frameworks for assessing and mining crop genetic diversity - Dongyan Zhao; Meng Lin; Cristiane H. Taniguti; Alexander M. Sandercock; Shufen Chen; Ebrahiem Babiker; Nahla V. Bassil; E. Charles Brummer; Jose Roberto Camacho; Warren Chatwin; Shu-Yun Chen; Shaun J. Clare; et al. (Theoretical and Applied Genetics, 2026)
Keymessage Standardized microhaplotype databases for eight diverse crops enable multiallelic analyses, comparative genetics, and breeding decisions. Abstract Microhaplotypes are short genomic segments that contain multiple tightly linked variants, providing multi-allelic data that can enhance genetic resolution compared to traditional biallelic single nucleotide polymorphism (SNP) markers. Here, we present the creation and utilization of separate microhaplotype databases for eight crop species representing diverse genome sizes, ploidy levels, and breeding systems. We developed a standardized, species-agnostic pipeline for processing, filtering, and databasing microhaplotypes generated using the DArTag targeted genotyping platform. To enhance user accessibility, we developed a no-code, user-friendly application, HapApp, that uses an R Shiny front-end interface to allow breeders and researchers to add unique, standardized microhaplotype identities from raw DArTag reports and iteratively update the existing crop-specific database with the newly discovered microhaplotypes. Selected case studies with these databases highlight the operational advantages of microhaplotypes, especially for challenging, highly heterozygous, or polyploid species. They offer an informative alternative to traditional biallelic SNP analyses for resolving population structures and improving linkage map ordering. This integrated framework provides a reproducible and scalable foundation for managing and exploiting microhaplotype data in plant breeding and genetic research, enabling robust cross-project comparisons and facilitating trait discovery in both simple and complex crop genomes, while enabling comparative genomics and cross-species functional transfer that accelerates genetic gains across all crop species.

Cadomian/Cenerian sources in Variscan granites from the Western Carpathians: Evidence from zircon geochronology, Hf-isotopes and whole-rock geochemistry - Igor Broska; Milan Kohút; Santosh Kumar; Sergii Kurylo; Maria Maraszewska; Keewook Yi; Shinae Lee; Youn Joong Jeong; Ľubica Puškelová (Lithos, 2026)

Surfactants as a strategy to enhance substrate uptake and transport in anaerobic bioreactors for process intensification - Henrique S. Dornelles; Giin-Yu Amy Tan; Emma Beirns; Theo Y.C. Lam; Maria A.T. Adorno; Carolina A. Sabatini; Maria B.A. Varesche; Po-Heng Lee (Chemical Engineering Journal, 2026)

Longitudinal wastewater-based surveillance of vancomycin-resistant Enterococci in tertiary-care hospitals - Emily Au; Nicole Acosta; Barbara J. Waddell; Jangwoo Lee; Kristine Du; R. Benson Weyant; Maria Bautista; Janine McCalder; Jennifer Van Doorn; Kashtin Low; September Stefani; Gail Visser; et al. (Science of The Total Environment, 2026)

Artificial intelligence for marine oil spill management: Recent advances and future directions - Ziyu Wang; Yawen Huang; Guorui Zhang; Zhihan Wang; Zhi Chen; Catherine N. Mulligan; S. Samuel Li; Maria Elektorowicz; Biao Li; Kenneth Lee; Chunjiang An (Marine Environmental Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Optimism predicts future economic mobility among hurricane maria migrants - Maria Duque; Yara Acaf; Christopher P. Salas-Wright; Mildred M. Maldonado-Molina; Pablo Montero-Zamora; Evelyn Gualdron; Mia Cisco; Sumeyra Sahbaz; Carolina Scaramutti-Gladfelter; Lawrence G. Watkins; Duyen H. Vo; Seo Woo Lee; et al. (Climate and Development, 2026)

Simulated impacts of irrigation, planting date, and cultivar maturity on soybean yield and water productivity in a humid subtropical climate - Mounica Talasila; Maria Morrogh Bernard; Chad Lee; Ole Wendroth; Thiago Berton Ferreira; Gerrit Hoogenboom; Montserrat Salmerón (Field Crops Research, 2026)

Technoeconomic analysis and life cycle assessment of purification processes for captured CO2 streams - Elisavet Anglou; Kinga Gołąbek; Jacob DeWitt; Yunjin Lee; Patritsia Maria Stathatou; Hai-Ying Chen; Carsten Sievers; Todd J. Toops; David S. Sholl; Fani Boukouvala (Chemical Engineering Journal, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The importance of nutritional nudges in restaurant food environments: Insights from two contrasting countries - Monica Diaz-Beltran; Kiwon Lee; Karen Byrd; Martha Lievano; Diana Maria Orozco-Soto; Jeremy Young (Food Quality and Preference, 2026)

Correction: Assessment of AAV/polyketal chimeric nanoparticles for ocular gene transduction using an animal model - Brenda Fernanda Moreira Castro; Margaret Lugin; Maria Carolina Andrade Guerra; Marina França Dias; Rebecca T. Lee; Armando Silva-Cunha; Young Jik Kwon; Silvia Ligório Fialho (Drug Delivery and Translational Research, 2026)

Assessment of AAV/polyketal chimeric nanoparticles for ocular gene transduction using an animal model - Brenda Fernanda Moreira Castro; Margaret Lugin; Maria Carolina Andrade Guerra; Marina França Dias; Rebecca T. Lee; Armando Silva-Cunha; Young Jik Kwon; Silvia Ligório Fialho (Drug Delivery and Translational Research, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Informing spatial conservation prioritization with species’ traits - Liam A. Trethowan; Laura Jennings; Haerul Arifin; Renata Borosova; Gemma L. C. Bramley; Marie Briggs; Osanna Chu; Ruth P. Clark; Sally Dawson; Kiran L. Dhanjal‐Adams; Yance de Freitas; James Hartup; et al. (Conservation Biology, 2026)
New Guinea, the most botanically diverse island on the planet, is the location for one of the boldest conservation initiatives. The Manokwari Declaration aims to achieve 70% conservation designation for the Bird's Head Peninsula. This is 40% higher than the 2022 Global Biodiversity Framework target. However, there is a lack of species occurrence data to support evidence of where biodiversity can be best protected. To address this, we integrated plant trait data from taxonomic descriptions in species occurrence models that can inform conservation planning. Inclusion of traits improved the performance of co‐occurrence models of ∼800 plant species across the 100,000‐km 2 landscape. Traits generally improved model performance, but not all traits contributed equally (e.g., leaf size and red flower color most improved accuracy of occurrence prediction). Likewise, trait‐parameterized models tended to be most useful with rare species occurrence prediction, but this was inconsistent among traits. Under 70% protection, three‐quarters of the areas selected conserved trait diversity. Critically, trait diversity also increased the chances that areas at high risk of deforestation were selected as conservation priorities. Overall, we found that plant species’ traits, often key parameters of ecosystem function and resilience, improved spatial conservation planning.

Metabolic dependencies and neural progenitor dysregulation: driving forces in paediatric high-grade glioma development - Yan Hay Grace Lee; Maria Tsoli; Yan Chuan Shi; Chi Kin Ip; David Ziegler (Cancer and Metastasis Reviews, 2026)
Paediatric high-grade gliomas (pHGGs) are the most lethal brain tumours in children, characterised by profound epigenetic dysregulation and limited treatment options. The 2021 WHO Classification has established a molecular framework that distinguishes pHGGs as biologically distinct from adult glioblastoma, recognising four major subtypes: H3K27-altered diffuse midline glioma, H3G34-mutant diffuse hemispheric glioma, infant-type hemispheric glioma, and the rare IDH-mutant gliomas. Each subtype exhibits unique epigenetic landscapes, metabolic dependencies, and therapeutic vulnerabilities, necessitating subtype-specific treatment strategies. This review explores the molecular classification of pHGGs and examines the critical role of the tumour microenvironment in disease progression. We focus on glioma stem cells as central drivers of tumour initiation, maintenance, and therapeutic resistance, highlighting their remarkable cellular plasticity and ability to dynamically transition between different states. Particular attention is given to metabolic reprogramming in pHGGs, including alterations in glucose and lipid metabolism, and the exceptional metabolic flexibility of glioma stem cells that enables adaptation to microenvironmental pressures. Importantly, we discuss the intimate crosstalk between metabolism and epigenetic regulation, whereby metabolites serve as essential cofactors for chromatin-modifying enzymes—exemplified by α-ketoglutarate maintaining low H3K27me3 in H3K27M tumours and 2-hydroxyglutarate driving hypermethylation in IDH-mutant gliomas. We review preclinical models that have advanced pHGG research and discuss emerging immunotherapeutic approaches, including CAR T-cell therapies and oncolytic viruses. By synthesising current understanding of pHGG biology, this review aims to identify promising therapeutic avenues that exploit the unique metabolic and epigenetic vulnerabilities of each molecular subtype.

Bacterial community and chemical contamination in high-latitude lake waters: a comparative study from the Svalbard and Antarctic Peninsula regions - Alessandro Ciro Rappazzo; Angelina Lo Giudice; Carmen Rizzo; Stefania Giannarelli; Lisa Ghezzi; Maurizio Azzaro; Warren Raymond Lee Cairns; Maria Papale (Environmental Research, 2026)

Alpha-defensins promote macrophage inflammatory activation via RNF31 signaling - Jungnam Lee; Naweed Mohammad; Seyoung Mun; Kyudong Han; Tammy Flagg-Dowie; Maria Magallon; Mark L. Brantly; Karina A. Serban (Genes & Genomics, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Wastewater-based surveillance of hepatitis A virus across municipalities and neighbourhoods in Alberta, Canada - R. Benson Weyant; Aito Ueno; Barbara Waddell; Jangwoo Lee; Tulika Bhardwaj; Nicole Acosta; Kevin Xiang; Shahrzad Sarabi; Stefania Bertazzon; Aidan Bender; Gail Visser; Janine McCalder; et al. (Science of The Total Environment, 2026)

Impact of conjugation on the rheological properties of pulse protein-polysaccharide mixtures - Pervin Ari Akin; Iris J. Joye; Maria G. Corradini; Matthew Nosworthy; Yolanda Brummer; Phillip Lee Wing; Steve W. Cui (Food Hydrocolloids, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Temporal dynamics of lake microbiota under nanoplastic and enrofloxacin stress - Katarzyna Lysik; Piotr Maszczyk; Marcin Lukasz Zebrowski; Sebastiano Gozzo; Jae-Seong Lee; Maria Pyznar; Javier Jimenez-Lamana; Joanna Szpunar; Bartosz Kiersztyn; Ewa Babkiewicz (Science of The Total Environment, 2026)

Changes in international copper ore trading relationships due to the impact of COVID-19 pandemic: Based on social network analysis - Woolrim Lee; Maria Valeria Aguinaga Fonseca; Yusa Qursillananda; Munyphakdey Koet; Seokhui Lee (Resources Policy, 2026)

Effect of controlled human Plasmodium falciparum infection on B cell subsets in individuals with different levels of malaria immunity - Pilar Requena; Gloria Patricia Gómez-Pérez; Matthew B. B. McCall; Diana Barrios; Ruth Aguilar; Julia Fernández-Morata; Marta Vidal; Joseph J. Campo; Carla Sanchez; Maria Yazdabankhsh; B. Kim Lee Sim; Stephen L. Hoffman; et al. (Medical Microbiology and Immunology, 2025)
Continuous exposure to Plasmodium falciparum (Pf) has been associated with alterations in B cells. We investigated the effect of controlled human malaria infection (CHMI) on B cell phenotypes in individuals with different Pf immunity status: malaria-naïve, immunized with PfSPZ-CVac and semi-immune (lifelong-exposed) volunteers. Compared to naïve, semi-immune but not vaccinated individuals, had increased baseline frequencies of immature B cells (CD19 + CD10 + ), active naive (IgD + CD27 − CD21 − ) B cells, active atypical (IgD − CD27 − CD21 − ) memory B cells (MBCs), active classical (IgD − CD27 + CD21 − ) MBCs and CD1c + -B cells but lower frequencies of some IgG + -B cells. The frequencies of CD1c + active atypical MBCs correlated positively with anti-Pf antibodies and negatively with circulating eotaxin levels, while the opposite was observed for IgG + resting atypical MBCs. During early blood-stage infection (day 11 after CHMI), there was an expansion of resting classical (IgD − CD27 + CD21 + ) MBCs in all three groups. Vaccination, compared to placebo, altered the effect of CHMI on B cells, showing a positive association with resting classical MBCs (β = 0.190, 95% CI 0.011–0.368) and active naïve-PD1 + (β = 0.637, 95% CI 0.058 to 1.217) frequencies, and a negative one with CD1c + resting atypical MBCs (β = − 0.328, 95% CI − 0.621 to − 0.032). In addition, the sickle cell trait in semi-immune subjects altered the effect of CHMI on several B cells. In conclusion, lifelong but not vaccine exposure to malaria was associated with increased frequencies of multiple B cell subsets, with higher and lower percentages of CD1c and IgG expressing-cells, respectively. A single infection (CHMI) induces changes in B cell frequencies and is modulated by sickle cell trait and malaria-immunity status. Clinical Trials Registration NCT01624961, NCT02115516, and NCT02237586.

Tailoring chickpea protein functionality for food applications through supercritical CO2 processing - Gomathy Sandhya Subramanian; Daryl Lee; Su Hui Lim; Sergey Gorelik; Celyne Halim; Ashley Lim; Shi Jie Ang; Dylan Hao Wen Swee; Uma Jingxin Tay; Sreenivasa Reddy Puniredd; Khin Yin Win; Yoganathan Kanagasundaram; et al. (Food Research International, 2025)

Self-powered biodegradable nerve conduits for synergistic ultrasound-driven electrical stimulation and smart drug release - Kavitha Gopal; Joonseok Lee; Se Rim Jang; So Yeun Choi; Nirmal Prashanth Maria Joseph Raj; Vignesh Krishnamoorthi Kaliannagounder; Chan Hee Park (Chemical Engineering Journal, 2025)

The Zoo Sphere of Influence Model - Sarah L. Spooner; Susan L. Walker; Simon Dowell; Mara Cristina Marques; Marina Somenzari; Fabiana Lopes Rocha; Eugenia Cordero-Schmidt; Charlotte Hughes; Christine Lee; Charlotte Smith; Jennifer Kelly; Linda Salim; et al. (Biological Conservation, 2025)

Giant ferralsol genesis in Brazilian dry forest - José João Lelis Leal de Souza; Mehmet Zeki Billor; Ming-Kuo Lee; Maria Daniely Freire Guerra; Daniel Kroehling Rodrigues Cardoso; Edvaldo Cardoso; Rafael Albuquerque Xavier; Bartolomeu Israel de Souza; Fabiana Monteiro de Oliveira; Christiane Farias da Fonseca (CATENA, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Genome-wide association of root growth angle, seminal root numbers, and leaf area in the synthetic hexaploid wheat diversity panel - Maria Khalid; Zoya Khalid; Zubair Ahmed; Lee Hickey; Awais Rasheed; Alvina Gul; Rabia Amir (Plant Gene, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Global trends in urban forest irrigation: Environmental influences, challenges and opportunities for sustainable practices across 109 cities worldwide - Manuel Esperon-Rodriguez; Rachael V Gallagher; Alessio Russo; Sally A Power; Pedro Calaza-Martínez; Tiago Capela Lourenço; Paloma Cariñanos; Ana Alice Eleuterio; Zhengfei Guo; Gervais Lee; Pierre Masselot; Robert I. Mcdonald; et al. (Sustainable Cities and Society, 2025)

A survey of duckweed species in Southern Italy provided first distribution records of the hybrid Lemna × mediterranea in nature - Leone Ermes Romano; Luca Braglia; Maria Adelaide Iannelli; Yuri Lee; Silvia Gianì; Floriana Gavazzi; Laura Morello (Perspectives in Plant Ecology, Evolution and Systematics, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Development and characterization of pectin films containing nanoemulsions of the essential oil from Thymus vulgaris for preserving salami - Cassia Duarte Oliveira; Maria das Graças Cardoso; Luciano de Souza; Sofia Lara Silva Vieira; Geraldo de Sousa Candido; Bruna Fernandes Andrade; Eduardo Alves; David Lee Nelson; Juliano Elvis de Oliveira; Eduardo Mendes Ramos (Food Chemistry, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Chronic fat consumption affects metabolic aspects of murine physiology and influences ovarian follicle atresia - Ayodeji Ojo Oteyola; Isadora Maria Sátiro de Oliveira; Jonathas Medeiros de Almeida; Lucas Carvalho Cardoso; Thais de Merici Domingues e Paula; Julia Meireles Nogueira; Jade Carceroni de Sousa Carvalho; Henrique Martins Nogueira; Brenda Lee Simas Porto; Ana Paula Lucas Mota; Paulo Henrique Almeida Campos-Junior; Erika Cristina Jorge; et al. (Reproductive Toxicology, 2025)

Reaping what we sow: Centering values in food systems transformations research - O. Care; Julie G. Zaehringer; Michael J. Bernstein; Mollie Chapman; Cecilie Friis; Sonia Graham; L. Jamila Haider; Mónica Hernández-Morcillo; Harry Hoffmann; Maria Lee Kernecker; Hannah Pitt; Verena Seufert (Ambio, 2025)
In many transdisciplinary research settings, a lack of attention to the values underpinning project aims can inhibit stakeholder engagement and ultimately slow or undermine project outcomes. As a research collective (The Careoperative), we have developed a set of four shared values through a facilitated visioning process, as central to the way we work together: care, reflexivity, inclusivity, and collectivity. In this paper, we explore the implications of a values-centered approach to collaboration in food system transformation research. The paper presents two cases that illustrate how researchers might approach centering values in practice. Where much research on food system transformation focuses on values of food system stakeholders, we contribute insights into the values of researchers in such transdisciplinary endeavors. Specifically, we argue that researchers working on sustainability transformations need to be better prepared to engage in such reflections and aspire to embody values aligned with the transformations they seek to research.

Better objective sleep quality is associated with higher gut microbiota richness in older adults - Maria Teresa Wijaya; Ji-Tseng Fang; Geng-Hao Liu; Yuan-Ming Yeh; Ning-Hung Chen; Chih-Ming Lin; Kuain-Yi Wu; Chih-Mao Huang; Shwu-Hua Lee; Tatia M. C. Lee (GeroScience, 2025)
Aging is associated with disrupted sleep patterns, such as fragmented sleep and reduced efficiency, leading to negative health outcomes. There is evidence of a bidirectional relationship between sleep and gut microbiota, which plays a key role in the gut-brain axis and overall health. However, studies on this relationship in older adults have limited generalizability and show conflicting results, highlighting the need for further research. This study aimed to investigate the associations between sleep quality and gut microbiota composition in healthy Chinese older adults using subjective and objective sleep measures to capture various aspects of sleep quality and explore potential impacts on emotional well-being and cognitive performance. Subjective sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, while objective sleep quality was measured with actigraphy. Gut microbiota sequencing was performed on stool samples. The results show a robust positive association between gut microbiota richness and objective sleep quality in older adults, independent of subjective sleep quality and demographics, lifestyle, and health covariates. However, no significant link was found between gut microbiota richness and subjective sleep quality. Specific taxa like Bacteroidetes, Ruminococcus , Collinsella , Veillonella , and Holdemania were tentatively linked to sleep quality. These findings emphasize the connection between sleep quality and gut microbiota composition in older adults with potential research and clinical implications, improving our understanding of the mechanisms underlying the sleep-gut microbiota relationship and guiding the development of interventions for improving both sleep quality and gut health in older adults.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Description of a novel coprophilous Lichtheimia (Mucoromycotina, Mucorales) species with notes on Lichtheimia species and an identification key for the genus - Mateus Oliveira da Cruz; Hyang Burm Lee; Thalline Rafhaella Leite Cordeiro; Francisca Robervânia Soares dos Santos; Maria Helena Alves; Thuong Thuong Thi Nguyen; Eleni Gentekaki; Vedprakash G. Hurdeal; André Luiz Cabral Monteiro de Azevedo Santiago (Mycological Progress, 2024)

Network analysis to reveal the most commonly detected compounds in predator-prey pairs in freshwater and marine mammals and fish in Europe - Nikiforos Alygizakis; Niki Kostopoulou; Georgios Gkotsis; Maria-Christina Nika; Anastasia Orfanioti; Kelsey Ng; Erasmia Bizani; Varvara Nikolopoulou; Alexander Badry; Andrew Brownlow; Cinzia Centelleghe; Elizabeth A. Chadwick; et al. (Science of The Total Environment, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Characterization and treatment of industrial laundry wastewaters: a review - Grégorio Crini; Dario Lacalamita; Eric Lichtfouse; Nadia Morin-Crini; Chong Liu; Lee D. Wilson; Lorenzo A. Picos-Corrales; Mabel Amen Akhere; Maria Sotiropoulou; Corina Bradu; Chiara Mongioví (Environmental Chemistry Letters, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Temporal trends of exposure to the herbicide glyphosate in the United States (2013–2018): Data from the National Health and Nutrition Examination Survey - Maria Ospina; Andre Schütze; Pilar Morales-Agudelo; Meghan Vidal; Lee-Yang Wong; Antonia M. Calafat (Chemosphere, 2024)

Lower body negative pressure as a research tool and countermeasure for the physiological effects of spaceflight: A comprehensive review - Phani Paladugu; Joshua Ong; Rahul Kumar; Ethan Waisberg; Nasif Zaman; Sharif Amit Kamran; Alireza Tavakkoli; Maria Chiara Rivolta; Nicolas Nelson; Taehwan Yoo; Vivian Paraskevi Douglas; Konstantinos Douglas; et al. (Life Sciences in Space Research, 2024)

Longitudinal gut microbiome dynamics in relation to age and senescence in a wild animal population - Sarah F. Worsley; Charli S. Davies; Chuen Zhang Lee; Maria‐Elena Mannarelli; Terry Burke; Jan Komdeur; Hannah L. Dugdale; David S. Richardson (Molecular Ecology, 2024)
In humans, gut microbiome (GM) differences are often correlated with, and sometimes causally implicated in, ageing. However, it is unclear how these findings translate in wild animal populations. Studies that investigate how GM dynamics change within individuals, and with declines in physiological condition, are needed to fully understand links between chronological age, senescence and the GM, but have rarely been done. Here, we use longitudinal data collected from a closed population of Seychelles warblers ( Acrocephalus sechellensis ) to investigate how bacterial GM alpha diversity, composition and stability are associated with host senescence. We hypothesised that GM diversity and composition will differ, and become more variable, in older adults, particularly in the terminal year prior to death, as the GM becomes increasingly dysregulated due to senescence. However, GM alpha diversity and composition remained largely invariable with respect to adult age and did not differ in an individual's terminal year. Furthermore, there was no evidence that the GM became more heterogenous in senescent age groups (individuals older than 6 years), or in the terminal year. Instead, environmental variables such as season, territory quality and time of day, were the strongest predictors of GM variation in adult Seychelles warblers. These results contrast with studies on humans, captive animal populations and some (but not all) studies on non‐human primates, suggesting that GM deterioration may not be a universal hallmark of senescence in wild animal species. Further work is needed to disentangle the factors driving variation in GM‐senescence relationships across different host taxa.

Circular genetic structure of the Abies nephrolepis species complex shaped by the circular landform of Northeast Asia - Myounghai Kwak; Koh Nakamura; Qiaoping Xiang; Jun Wen; Eun Sil Lee; Jaram Hong; Nataliya Kovtonyuk; Maria Kryukova; Olga Korchagina; Kyung Ah Koo; Masakazu G. Iwaizumi; Byoung Yoon Lee; et al. (Journal of Biogeography, 2024)
Aim Pinaceae have been noted for their tendency towards reticulation as a result of interspecific hybridization. Here, we demonstrated the phylogeographic dynamics of the native Northeast Asian sub‐alpine conifer, Abies nephrolepis species complex (ANSC), evolving in circular overlaps along the Northeast Asian landform, which functions as a corridor with the sea, thus acting as a geographic barrier. Location Northeast Asia: the Korean Peninsula, Japanese Archipelago, Russian Far East and northeastern China. Taxon Abies nephrolepis species complex (Family Pinaceae, Genus Abies , Section Balsamea , Abies nephrolepis, A. koreana, A. veitchii and A. sachalinensis ). Methods A total of 728 individuals from 38 ANSC populations were analysed using multiplexed inter‐simple sequence repeat genotyping by sequencing to capture variations in biparental nuclear genomes. Eight mitochondrial regions and eight chloroplast regions of each individual were sequenced using the MiSeq platform and Sanger sequencing. Species distribution models were generated. Results Bayesian clustering with 507 nuclear single nucleotide polymorphisms and the discrepancy between cytoplasmic and nuclear genome lineages implied contemporary and ancient connections between neighbouring species in the form of circular overlap. This genetic connectivity was supported by principal component analysis. Strong correlations between genetic distance and geographic distance were observed, suggesting that gene flow occurs through a continuous chain around the sea. We also found that gene flow direction and intensity changed over time, with support from palaeodistribution modelling. Conclusion Past hybridization events were captured in cytoplasmic genomes, generating heterogeneity across maternal ancestries. This intensive phylogeographic study demonstrates speciation with incomplete reproductive isolation (continuous gene flow) among neighbouring species with an alteration of the direction and intensity of gene flow due to climate change. The divergence of ANSC due to repeated isolation and reconnection caused by heterogenous physiological environments and climate fluctuation provides a model to solve evolutionary scenarios for reticulate evolution in Pinaceae and other plants.

An algorithm for modelling escalator fixed loss energy for PHM and sustainable energy usage - Xuwen Hu; Jiaqi Qiu; Yu Lin; Inez Maria Zwetsloot; William Ka Fai Lee; Edmond Yin San Yeung; Colman Yiu Wah Yeung; Chris Chun Long Wong (Energy and Buildings, 2024)

Microbial synergies drive simultaneous biodegradation of ethoxy and alkyl chains of Nonylphenol Ethoxylate in fluidized bed reactors - Henrique S. Dornelles; Carolina A. Sabatini; Maria A.T. Adorno; Edson L. Silva; Po-Heng Lee; Maria Bernadete A. Varesche (Chemosphere, 2024)

Parity in bacterial communities and resistomes: Microplastic and natural organic particles in the Tyrrhenian Sea - Andrea Di Cesare; Maria Belen Sathicq; Tomasa Sbaffi; Raffaella Sabatino; Dario Manca; Florian Breider; Sylvain Coudret; Lee J. Pinnell; Jeffrey W. Turner; Gianluca Corno (Marine Pollution Bulletin, 2024)

Does salinity mediate the toxicity of perfluorooctanesulfonic acid (PFOS) in an estuarine fish? - Lucy E. Burcham; Tyler D. Hoskins; Elizabeth B. Allmon; Meredith N. Scherer; Anna G. Bushong; Matthew T. Hamilton; Sini Macheri; Grace S. Coogan; Youn J. Choi; Linda S. Lee; Maria S. Sepúlveda (Marine Pollution Bulletin, 2024)

Risk factors associated with indicators of dehydration among migrant farmworkers - Chibuzor Abasilim; Lee S. Friedman; Miranda Carver Martin; Dana Madigan; Jose Perez; Maria Morera; Antonio Tovar; Fritz Roka; Nezahuacoyotl Xiuhtecutli; Linda Forst; Paul Monaghan (Environmental Research, 2024)

Enhancing thermoelectric performance of solution-processed polycrystalline SnSe with PbSe nanocrystals - Yu Liu; Seungho Lee; Christine Fiedler; Maria Chiara Spadaro; Cheng Chang; Mingquan Li; Min Hong; Jordi Arbiol; Maria Ibáñez (Chemical Engineering Journal, 2024)

Landscape of global urban environmental resistome and its association with local socioeconomic and medical status - Jun Wu; Yige Hu; Michael H. Perlin; David Danko; Jun Lu; Manuela Oliveira; Johannes Werner; Maria M. Zambrano; Maria A. Sierra; Olayinka O. Osuolale; Paweł Łabaj; Nicolás Rascovan; et al. (Science China Life Sciences, 2024)

Recreation and its synergies and trade-offs with other ecosystem services of Alpine and pre-Alpine grasslands - Thomas M.Schmitt; Maria Haensel; Andrea Kaim; Heera Lee; Sophie Reinermann; Thomas Koellner (Regional Environmental Change, 2024)
Alpine and pre-Alpine grasslands provide numerous ecosystem services including provisioning services (e.g. fodder production), regulating services (e.g. soil erosion reduction), and cultural services (e.g. recreation). While intensively managed grasslands specifically target the production of fodder, more extensively used grasslands are known for being hotspots of biodiversity. However, there is a need to better understand the relationship among the supply of ecosystem services, specifically regarding the use of grasslands for cultural ecosystem services such as recreation. In this study, we investigated the synergies and trade-offs of ecosystem services and analyzed underlying variables related to the recreational use of grasslands. We investigated the supply of recreation (indicated by Photo-User-Days from geo-tagged photos on grasslands), fodder production (indicated by yield), and regulating and habitat ecosystem services (indicated by agri-environmental payments), and analyzed their relationship to management-related variables with a Redundancy Analysis. To better explain the recreational use of grasslands, we further analyzed how environmental and infrastructural features influence the occurrence of Photo-User-Days with a hurdle regression. Finally, we conducted spatial analyses to understand the distribution of Photo-User-Days in space. We found a weak but significant negative relationship between Photo-User-Days and yield, which implies that people slightly prefer extensive grassland to intensive grassland for recreation. Our results also show that agri-environmental schemes targeted towards extensive grassland management can positively influence the recreational use. Other factors, such as proximity to touristic features (e.g. castles), presence of infrastructural features (e.g. cable cars), and environmental characteristics (e.g. low share of croplands, distance to forests), also influenced the spatial distribution of photos on grasslands. The importance of these factors underscores the value of grasslands as a component of the cultural landscape for recreational purposes. These results also suggest that cultural ecosystem services of grasslands can be considered to be co-produced by natural, social, and infrastructural components. The study further discusses limitations to the explanatory power of geo-tagged photo analysis to determine the wide range of cultural ecosystem services of grasslands. We conclude that grasslands play an important role for recreation in (pre-)Alpine landscapes, which can also be effectively supported through targeted agri-environmental payments.

Exfoliated defects-rich g-C3N4 nanosheets heterointerface engineering with CuCo2O4 as promising bifunctional electrocatalysts for seawater splitting - Shrine Maria Nithya Jeghan; Boseok Seo; Hyeonwook Son; Sang Woo Joo; Minkyu Kim; Gibaek Lee (Chemical Engineering Journal, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Rational confinement of ternary layered double hydroxide within three-dimensional graphene aerogel: An electrochemical tool for propyl gallate sensing - Megha Maria Stanley; Balasubramanian Sriram; Sea-Fue Wang; Abhikha Sherlin; Sakthivel Kogularasu; Yen-Yi Lee; Mary George (Chemical Engineering Journal, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Public opinion about solar radiation management: A cross-cultural study in 20 countries around the world - Nadja Contzen; Goda Perlaviciute; Linda Steg; Sophie Charlotte Reckels; Susana Alves; David Bidwell; Gisela Böhm; Marino Bonaiuto; Li-Fang Chou; Victor Corral-Verdugo; Federica Dessi; Thomas Dietz; et al. (Climatic Change, 2024)
Some argue that complementing climate change mitigation measures with solar radiation management (SRM) might prove a last resort to limit global warming to 1.5 °C. To make a socially responsible decision on whether to use SRM, it is important to consider also public opinion, across the globe and particularly in the Global South, which would face the greatest risks from both global warming and SRM. However, most research on public opinion about SRM stems from the Global North. We report findings from the first large-scale, cross-cultural study on the public opinion about SRM among the general public ( N = 2,248) and students ( N = 4,583) in 20 countries covering all inhabited continents, including five countries from the Global South and five ‘non-WEIRD’ (i.e. not Western, Educated, Industrialised, Rich, and Democratic) countries from the Global North. As public awareness of SRM is usually low, we provided participants with information on SRM, including key arguments in favour of and against SRM that appear in the scientific debate. On average, acceptability of SRM was significantly higher in the Global South than in the ‘non-WEIRD’ Global North, while acceptability in the ‘WEIRD’ Global North was in between. However, we found substantial variation within these clusters, especially in the ‘non-WEIRD’ Global North, suggesting that countries do not form homogenous clusters and should thus be considered individually. Moreover, the average participants’ views, while generally neither strong nor polarised, differed from some expert views in important ways, including that participants perceived SRM as only slightly effective in limiting global warming. Still, our data suggests overall a conditional, reluctant acceptance. That is, while on average, people think SRM would have mostly negative consequences, they may still be willing to tolerate it as a potential last resort to fight global warming, particularly if they think SRM has only minor negative (or even positive) impacts on humans and nature.

Nanoparticles with intermediate hydrophobicity polarize macrophages to plaque-specific Mox phenotype via Nrf2 and HO-1 activation - Shumei Zhai; Xianzhi Zhang; Mingdi Jiang; Yujia Liu; Guangbo Qu; Xiaomiao Cui; Cristina-Maria Hirschbiegel; Yuanchang Liu; Colby Alves; Yi-Wei Lee; Guibin Jiang; Bing Yan; et al. (Journal of Hazardous Materials, 2024)

How values and perceptions shape farmers' biodiversity management: Insights from ten European countries - Fabian Klebl; Anton Parisi; Kati Häfner; Anneli Adler; Sílvia Barreiro; Flaviu Valentin Bodea; Viviane Brönnimann; Jan Peter Reinier de Vries; Alice Dos Santos; Amelia S.C. Hood; Indrek Melts; Răzvan Popa; et al. (Biological Conservation, 2024)

A point-of-care pilot randomized intervention to connect patients with cancer-induced financial toxicity to telehealth financial counseling - Caterina Alacevich; Anna Maria Abi Nehme; Ji-Hyun Lee; Derek Li; Erin M. Mobley; Julia L. Close; Thomas J. George; Jennifer H. LeLaurin; Young-Rock Hong; Elizabeth A. Shenkman; Michael S. Gutter; Ramzi G. Salloum (Cancer Causes & Control, 2024)

Potential of microbial control agents in a strategy against Duponchelia fovealis Zeller (Lepidoptera: Crambidae) - Thaísa Siqueira Da Luz; Carolina Gracia Poitevin; Rubens Candido Zimmermann; Jason Lee Furuie; Edson José Mazarotto; Maria Aparecida Cassilha Zawadneak; Joatan Machado da Rosa; Carlos Eduardo Nogueira Martins; Ida Chapaval Pimentel (Crop Protection, 2024)

Persistence, Health Care Resource Utilization, and Costs Among OnabotulinumtoxinA-Treated Patients With Cervical Dystonia in the US - Khashayar Dashtipour; Marjan Sadeghi; Maria Heath; Andrew Rava; Jinjie Liu; Haiyan Sun; Yanan Dong; Jae Lee (Toxicon, 2024)

Experimental and computational fluid-structure interaction analysis and optimization of Deep-V planing-hull grillage panels subject to slamming loads – Part II: Irregular waves - Evan J. Lee; Matteo Diez; Emily L. Harrison; Minyee J. Jiang; Lawrence A. Snyder; Ann Marie R. Powers; Raymond J. Bay; Andrea Serani; Maria L. Nadal; Eric R. Kubina; Frederick Stern (Ocean Engineering, 2024)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Extinction risks and mitigation for a megaherbivore, the giraffe, in a human‐influenced landscape under climate change - Monica L. Bond; Derek E. Lee; Maria Paniw (Global Change Biology, 2023)
Megaherbivores play “outsized” roles in ecosystem functioning but are vulnerable to human impacts such as overhunting, land‐use changes, and climate extremes. However, such impacts—and combinations of these impacts—on population dynamics are rarely examined using empirical data. To guide effective conservation actions under increasing global‐change pressures, we developed a socially structured individual‐based model (IBM) using long‐term demographic data from female giraffes ( Giraffa camelopardalis ) in a human‐influenced landscape in northern Tanzania, the Tarangire Ecosystem. This unfenced system includes savanna habitats with a wide gradient of anthropogenic pressures, from national parks, a wildlife ranch and community conservation areas, to unprotected village lands. We then simulated and projected over 50 years how realistic environmental and land‐use management changes might affect this metapopulation of female giraffes. Scenarios included: (1) anthropogenic land‐use changes including roads and agricultural/urban expansion; (2) reduction or improvement in wildlife law enforcement measures; (3) changes in populations of natural predators and migratory alternative prey; and (4) increases in rainfall as predicted for East Africa. The factor causing the greatest risk of rapid declines in female giraffe abundance in our simulations was a reduction in law enforcement leading to more poaching. Other threats decreased abundances of giraffes, but improving law enforcement in both of the study area's protected areas mitigated these impacts: a 0.01 increase in giraffe survival probability from improved law enforcement mitigated a 25% rise in heavy rainfall events by increasing abundance 19%, and mitigated the expansion of towns and blockage of dispersal movements by increasing abundance 22%. Our IBM enabled us to further quantify fine‐scale abundance changes among female giraffe social communities, revealing potential source–sink interactions within the metapopulation. This flexible methodology can be adapted to test additional ecological questions in this landscape, or to model populations of giraffes or other species in different ecosystems.

Wastewater-based surveillance can be used to model COVID-19-associated workforce absenteeism - Nicole Acosta; Xiaotian Dai; Maria A. Bautista; Barbara J. Waddell; Jangwoo Lee; Kristine Du; Janine McCalder; Puja Pradhan; Chloe Papparis; Xuewen Lu; Thierry Chekouo; Alexander Krusina; et al. (Science of The Total Environment, 2023)

Campus node-based wastewater surveillance enables COVID-19 case localization and confirms lower SARS-CoV-2 burden relative to the surrounding community - Jangwoo Lee; Nicole Acosta; Barbara J. Waddell; Kristine Du; Kevin Xiang; Jennifer Van Doorn; Kashtin Low; Maria A. Bautista; Janine McCalder; Xiaotian Dai; Xuewen Lu; Thierry Chekouo; et al. (Water Research, 2023)

BioDeepTime: A database of biodiversity time series for modern and fossil assemblages - Jansen Smith; Marina C. Rillo; Ádám T. Kocsis; Maria Dornelas; David Fastovich; Huai‐Hsuan M. Huang; Lukas Jonkers; Wolfgang Kiessling; Qijian Li; Lee Hsiang Liow; Miranda Margulis‐Ohnuma; Stephen Meyers; et al. (Global Ecology and Biogeography, 2023)
Motivation We have little understanding of how communities respond to varying magnitudes and rates of environmental perturbations across temporal scales. BioDeepTime harmonizes assemblage time series of presence and abundance data to help facilitate investigations of community dynamics across timescales and the response of communities to natural and anthropogenic stressors. BioDeepTime includes time series of terrestrial and aquatic assemblages of varying spatial and temporal grain and extent from the present‐day to millions of years ago. Main Types of Variables Included BioDeepTime currently contains 7,437,847 taxon records from 10,062 assemblage time series, each with a minimum of 10 time steps. Age constraints, sampling method, environment and taxonomic scope are provided for each time series. Spatial Location and Grain The database includes 8752 unique sampling locations from freshwater, marine and terrestrial ecosystems. Spatial grain represented by individual samples varies from quadrats on the order of several cm 2 to grid cells of ~100 km 2 . Time Period and Grain BioDeepTime in aggregate currently spans the last 451 million years, with the 10,062 modern and fossil assemblage time series ranging in extent from years to millions of years. The median extent of modern time series is 18.7 years and for fossil series is 54,872 years. Temporal grain, the time encompassed by individual samples, ranges from days to tens of thousands of years. Major Taxa and Level of Measurement The database contains information on 28,777 unique taxa with 4,769,789 records at the species level and another 271,218 records known to the genus level, including time series of benthic and planktonic foraminifera, coccolithophores, diatoms, ostracods, plants (pollen), radiolarians and other invertebrates and vertebrates. There are to date 7012 modern and 3050 fossil time series in BioDeepTime. Software Format SQLite, Comma‐separated values.

Towards standardized reporting and failure classification of safety equipment: Semi-automated classification of failure data for safety equipment in the operating phase - Shenae Lee; Maria Vatshaug Ottermo; Stein Hauge; Mary Ann Lundteigen (Process Safety and Environmental Protection, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Consensus Paper: Cerebellum and Ageing - Angelo Arleo; Martin Bareš; Jessica A. Bernard; Hannah R. Bogoian; Muriel M. K. Bruchhage; Patrick Bryant; Erik S. Carlson; Chetwyn C. H. Chan; Liang-Kung Chen; Chih-Ping Chung; Vonetta M. Dotson; Pavel Filip; et al. (The Cerebellum, 2023)

Co-exposure of iron oxide nanoparticles with glyphosate herbicides in Poecilia reticulata: Fish liver damages is reversible during iron accumulation and elimination period - João Marcos de Lima-Faria; Victória Costa da Silva; Lee Chen Chen; Diego Stéfani Teodoro Martinez; Simone Maria Teixeira de Sabóia-Morais (Chemosphere, 2023)

Spatial variation in the benthic community structure of a coral reef system in the central Philippines: Highlighting hard coral, octocoral, and sponge assemblages - Jue Alef A. Lalas; Geminne G. Manzano; Lee Arraby B. Desabelle; Maria Vanessa Baria-Rodriguez (Regional Studies in Marine Science, 2023)

Biomass Production and Nutrient Removal by Perennial Energy Grasses Produced on a Wet Marginal Land - Danielle R. Cooney; Nictor Namoi; Colleen Zumpf; Soo-Hyun Lim; Maria Villamil; Robert Mitchell; D. K. Lee (BioEnergy Research, 2023)
Growing dedicated bioenergy crops on marginal land can provide beneficial outcomes including biomass production and energy, resource management, and ecosystem services. We investigated the effects of harvest timing (peak standing crop [PEAK] or after killing frost [KF]) and nitrogen (N) fertilizer rates (0, 56, and 112 kg N ha −1 ) on yield, nutrient concentrations, and nutrient removal rates of perennial grasses on a wet marginal land. We evaluated three monocultures, including switchgrass ( Panicum virgatum L., SW), Miscanthus x giganteus (MG), prairie cordgrass ( Spartina pectinata Link, PCG), and a polyculture mixture of big bluestem ( Andropogon gerardii Vitman), Indiangrass ( Sorghastrum nutans (L.) Nash), and sideoats grama ( Bouteloua curtipendula Torr., MIX). Increasing the application of N did correlate with increased biomass, concentration, and subsequent removal of nutrients across almost all treatment combinations. In all grass treatments except MG, PEAK harvesting increased yield and nutrient removal. At PEAK harvest, switchgrass is ideal for optimizing both biomass production and nutrient removal. While our results also suggest short-term plasticity for farmers when selecting harvest timing for optimal nutrient removal, KF harvest is recommended to ensure long-term stand longevity and adequate nutrient removal. If the KF harvest is adopted, MG would be the ideal option for optimizing biomass yield potential. Additionally, we found that the yield of polyculture did not vary much with harvest timing, suggesting better yield stability. Future studies should give consideration for long-term evaluation of polyculture mixtures to assess their biomass yields and nutrient removal capacities.

Corrigendum to “Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification” [Biol. Conserv. 281 (2023) 109994] - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Immunomodulatory and Anti-inflammatory effect of Neural Stem/Progenitor Cells in the Central Nervous System - Wei Ni; Murugan Ramalingam; Yumeng Li; Jeong-Hui Park; Khandmaa Dashnyam; Jung-Hwan Lee; Nora Bloise; Lorenzo Fassina; Livia Visai; Maria Gabriella Cusella De Angelis; Jose Luis Pedraz; Hae-Won Kim; et al. (Stem Cell Reviews and Reports, 2023)

Bringing Antarctica to the lab: a polar desert environmental chamber to study the response of Antarctic microbial communities to climate change - Maria R. Monteiro; Alexis J. Marshall; Charles K. Lee; Ian R. McDonald; S. Craig Cary (Polar Biology, 2023)
Polar deserts contain unique and sensitive communities responsive to climate-associated habitat changes. However, unlike temperate desert ecosystems, characterizing and predicting the responses of polar ecosystems to environmental change remains a significant challenge due to logistical constraints. Here we aim to demonstrate the use of a custom-designed Polar Desert Environmental Chamber (PDEC) to perform off-continent experimental ecological research. We did so by characterizing the structure and composition of arid edaphic bacterial communities collected from the McMurdo Dry Valleys during a simulated wetting event. The results were discussed in light of previous field observations. Rapid structural and compositional changes were observed during wetting and re-drying treatments. Those were driven by changes in the relative abundance of coexisting taxa, which fluctuated asynchronously over time in response to the treatments. While selection was the main ecological factor influencing communities during dry conditions or the initial wetting, with prolonged exposure to wetness, neutral processes began to drive community assembly. Ultimately, these observations reflect different adaptative responses from microbial taxa to water stress, which can be argued as beneficial to increasing resilience in polar deserts. Our findings demonstrate that experiments conducted in PDEC provide valuable contextual data on community response to environmental change and can accelerate our ability to assess biological thresholds to change within polar desert ecosystems. We advocate that, with careful consideration of key emulated environmental attributes, laboratory-based Antarctic research can complement fieldwork to achieve a nuanced and evidence-based understanding of the ecology of Antarctica’s ice-free regions.

Occurrence and implications of per and polyfluoroalkyl substances in animal feeds used in laboratory toxicity testing - Youn Jeong Choi; Linda S. Lee; Tyler D. Hoskins; Mahsa Modiri Gharehveran; Maria S. Sepúlveda (Science of The Total Environment, 2023)

Metabolomics of the interaction between a consortium of entomopathogenic fungi and their target insect: Mechanisms of attack and survival - Andressa Katiski da Costa Stuart; Jason Lee Furuie; Thais Regiani Cataldi; Rodrigo Makowiecky Stuart; Maria Aparecida Cassilha Zawadneak; Carlos Alberto Labate; Ida Chapaval Pimentel (Pesticide Biochemistry and Physiology, 2023)

PFAS release from wastewater residuals as a function of composition and production practices - Caleb R. Gravesen; Linda S. Lee; Youn Jeong Choi; Maria L. Silveira; Jonathan D. Judy (Environmental Pollution, 2023)

College Students’ Awareness of the Link Between Human Papillomavirus (HPV) and HPV-Associated Cancers - Maria C. Franca; Valerie E. Boyer; Mary A. Gerend; Minjee Lee; Kelli D. Whittington; Stacey L. McKinney; Sandra K. Collins; Richard C. McKinnies; Eric Adjei Boakye (Journal of Cancer Education, 2023)

Response of soil health indicators to dung, urine and mineral fertilizer application in temperate pastures - Carmen Segura; Claire Horrocks; Maria Lopez-Aizpun; Martin S.A. Blackwell; Tegan Darch; Jess Hood; Kate Le Cocq; Graham A. McAuliffe; Michael R.F. Lee; Laura Cardenas (Journal of Environmental Management, 2023)

Prevalence of and factors associated with long-term sick leave in working-age adults with osteoarthritis: a retrospective cohort study conducted in Germany - Louis Jacob; Ai Koyanagi; Josep Maria Haro; Jae Il Shin; Lee Smith; Marcel Konrad; Karel Kostev (International Archives of Occupational and Environmental Health, 2023)

Antifungal activity of essential oils and their combinations against storage fungi - Rubens Candido Zimmermann; Carolina Gracia Poitevin; Thaisa Siqueira da Luz; Edson José Mazarotto; Jason Lee Furuie; Carlos Eduardo Nogueira Martins; Wanderlei do Amaral; Roger Raupp Cipriano; Joatan Machado da Rosa; Ida Chapaval Pimentel; Maria A. C. Zawadneak (Environmental Science and Pollution Research, 2023)

What determines accuracy of chemical identification when using microspectroscopy for the analysis of microplastics? - Hannah De Frond; Win Cowger; Violet Renick; Susanne Brander; Sebastian Primpke; Suja Sukumaran; Dounia Elkhatib; Steve Barnett; Maria Navas-Moreno; Keith Rickabaugh; Florian Vollnhals; Bridget O'Donnell; et al. (Chemosphere, 2023)

Biochemical metabolomic profiling of the Crown-of-Thorns Starfish (Acanthaster): New insight into its biology for improved pest management - Omar Mendoza-Porras; Thao V. Nguyen; Rohan M. Shah; Peter Thomas-Hall; Lee Bastin; Dione J. Deaker; Cherie A. Motti; Maria Byrne; David J. Beale (Science of The Total Environment, 2023)

A hybrid FV/FD scheme for a novel conservative form of extended Boussinesq equations for waves in porous media - Van Nghi Vu; Maria Kazolea; Van Khoi Pham; Changhoon Lee (Ocean Engineering, 2023)

Integrated modeling for simulating sediment production and transport in agricultural landscapes - Sanghyun Lee; Maria L. Chu; Jorge A. Guzman; Dennis C. Flanagan; Daniel N. Moriasi; Ann-Marie Fortuna; Patrick Starks (Environmental Modelling & Software, 2023)

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

The association of COVID-19 incidence with temperature, humidity, and UV radiation – A global multi-city analysis - Luise Nottmeyer; Ben Armstrong; Rachel Lowe; Sam Abbott; Sophie Meakin; Kathleen M. O'Reilly; Rosa von Borries; Rochelle Schneider; Dominic Royé; Masahiro Hashizume; Mathilde Pascal; Aurelio Tobias; et al. (Science of The Total Environment, 2023)

Piecemeal stewardship activities miss numerous social and environmental benefits associated with culturally appropriate ways of caring for country - Silva Larson; Diane Jarvis; Natalie Stoeckl; Ryan Barrowei; Bessie Coleman; David Groves; Joshua Hunter; Maria Lee; Michael Markham; Anna Larson; Glenn Finau; Michael Douglas (Journal of Environmental Management, 2023)

In vitro and in vivo efficacy of poly(lactic acid) nanofiber packaging containing essential oils from Ocimum basilicum L. and Ocimum gratissimum L. against Aspergillus carbonarius and Aspergillus niger in table grapes - Rafaela Magalhães Brandão; Luís Roberto Batista; Juliano Elvis de Oliveira; Richard Bispo Barbosa; David Lee Nelson; Maria Graças Cardoso (Food Chemistry, 2023)

Review of Environmental Monitoring by Means of Radio Waves in the Polar Regions: From Atmosphere to Geospace - Lucilla Alfonsi; Nicolas Bergeot; Pierre J. Cilliers; Giorgiana De Franceschi; Lisa Baddeley; Emilia Correia; Domenico Di Mauro; Carl-Fredrik Enell; Mark Engebretson; Reza Ghoddousi-Fard; Ingemar Häggström; Young-bae Ham; et al. (Surveys in Geophysics, 2022)
The Antarctic and Arctic regions are Earth's open windows to outer space. They provide unique opportunities for investigating the troposphere–thermosphere–ionosphere–plasmasphere system at high latitudes, which is not as well understood as the mid- and low-latitude regions mainly due to the paucity of experimental observations. In addition, different neutral and ionised atmospheric layers at high latitudes are much more variable compared to lower latitudes, and their variability is due to mechanisms not yet fully understood. Fortunately, in this new millennium the observing infrastructure in Antarctica and the Arctic has been growing, thus providing scientists with new opportunities to advance our knowledge on the polar atmosphere and geospace. This review shows that it is of paramount importance to perform integrated, multi-disciplinary research, making use of long-term multi-instrument observations combined with ad hoc measurement campaigns to improve our capability of investigating atmospheric dynamics in the polar regions from the troposphere up to the plasmasphere, as well as the coupling between atmospheric layers. Starting from the state of the art of understanding the polar atmosphere, our survey outlines the roadmap for enhancing scientific investigation of its physical mechanisms and dynamics through the full exploitation of the available infrastructures for radio-based environmental monitoring.

A global analysis of viviparity in squamates highlights its prevalence in cold climates - Anna Zimin; Sean V. Zimin; Richard Shine; Luciano Avila; Aaron Bauer; Monika Böhm; Rafe Brown; Goni Barki; Gabriel Henrique de Oliveira Caetano; Fernando Castro Herrera; David G. Chapple; Laurent Chirio; et al. (Global Ecology and Biogeography, 2022)
Aim Viviparity has evolved more times in squamates than in any other vertebrate group; therefore, squamates offer an excellent model system in which to study the patterns, drivers and implications of reproductive mode evolution. Based on current species distributions, we examined three selective forces hypothesized to drive the evolution of squamate viviparity (cold climate, variable climate and hypoxic conditions) and tested whether viviparity is associated with larger body size. Location Global. Time period Present day. Taxon Squamata. Methods We compiled a dataset of 9061 squamate species, including their distributions, elevation, climate, body mass and reproductive modes. We applied species‐level and assemblage‐level approaches for predicting reproductive mode, both globally and within biogeographical realms. We tested the relationships of temperature, interannual and intra‐annual climatic variation, elevation (as a proxy for hypoxic conditions) and body mass with reproductive mode, using path analyses to account for correlations among the environmental predictors. Results Viviparity was strongly associated with cold climates at both species and assemblage levels, despite the prevalence of viviparity in some warm climates. Viviparity was not clearly correlated with climatic variability or elevation. The probability of being viviparous exhibited a weak positive correlation with body size. Conclusions Although phylogenetic history is important, potentially explaining the occurrence of viviparous species in regions that are warm at present, current global squamate distribution is characterized by a higher relative abundance of viviparity in cold environments, supporting the prediction of the “cold‐climate” hypothesis. The roles of climatic variation and hypoxia are less important and not straightforward. Elevation probably exerts various selective pressures and influences the prevalence of viviparity primarily through its effect on temperature rather than on oxygen concentration.

Kinetic, thermodynamic and physical-chemical study of the removal of copper from cachaça using coconut fibers - Richard Bispo Barbosa; Zuy Maria Magriotis; Ana Paula Andrade Gândara; Wilder Douglas Santiago; Gabriela Fontes Alvarenga; Rafaela Magalhães Brandão; Renan Elan da Silva Oliveira; Alex Rodrigues Silva Caetano; David Lee Nelson; Maria das Graças Cardoso (Food Additives & Contaminants: Part A, 2022)

Effects of meteorological and land surface modeling uncertainty on errors in winegrape ET calculated with SIMS - Conor T. Doherty; Lee F. Johnson; John Volk; Meagan S. Mauter; Nicolas Bambach; Andrew J. McElrone; Joseph G. Alfieri; Lawrence E. Hipps; John H. Prueger; Sebastian J. Castro; Maria Mar Alsina; William P. Kustas; et al. (Irrigation Science, 2022)
Characterization of model errors is important when applying satellite-driven evapotranspiration (ET) models to water resource management problems. This study examines how uncertainty in meteorological forcing data and land surface modeling propagate through to errors in final ET data calculated using the Satellite Irrigation Management Support (SIMS) model, a computationally efficient ET model driven with satellite surface reflectance values. The model is applied to three instrumented winegrape vineyards over the 2017–2020 time period and the spatial and temporal variation in errors are analyzed. We illustrate how meteorological data inputs can introduce biases that vary in space and at seasonal timescales, but that can persist from year to year. We also observe that errors in SIMS estimates of land surface conductance can have a particularly strong dependence on time of year. Overall, meteorological inputs introduced RMSE of 0.33–0.65 mm/day (7–27%) across sites, while SIMS introduced RMSE of 0.55–0.83 mm/day (19–24%). The relative error contribution from meteorological inputs versus SIMS varied across sites; errors from SIMS were larger at one site, errors from meteorological inputs were larger at a second site, and the error contributions were of equal magnitude at the third site. The similar magnitude of error contributions is significant given that many satellite-driven ET models differ in their approaches to estimating land surface conductance, but often rely on similar or identical meteorological forcing data. The finding is particularly notable given that SIMS makes assumptions about the land surface (no soil evaporation or plant water stress) that do not always hold in practice. The results of this study show that improving SIMS by eliminating these assumptions would result in meteorological inputs dominating the error budget of the model on the whole. This finding underscores the need for further work on characterizing spatial uncertainty in the meteorological forcing of ET.

Prevalence of and factors associated with long-term sick leave in working-age adults with chronic low back pain in Germany - Louis Jacob; Ai Koyanagi; Lee Smith; Jae Il Shin; Josep Maria Haro; Tilman Garthe; Karel Kostev (International Archives of Occupational and Environmental Health, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Resilient consumers accelerate the plant decomposition in a naturally acidified seagrass ecosystem - Juhyung Lee; Maria Cristina Gambi; Kristy J. Kroeker; Marco Munari; Kabir Peay; Fiorenza Micheli (Global Change Biology, 2022)
Anthropogenic stressors are predicted to alter biodiversity and ecosystem functioning worldwide. However, scaling up from species to ecosystem responses poses a challenge, as species and functional groups can exhibit different capacities to adapt, acclimate, and compensate under changing environments. We used a naturally acidified seagrass ecosystem (the endemic Mediterranean Posidonia oceanica ) as a model system to examine how ocean acidification (OA) modifies the community structure and functioning of plant detritivores, which play vital roles in the coastal nutrient cycling and food web dynamics. In seagrass beds associated with volcanic CO 2 vents (Ischia, Italy), we quantified the effects of OA on seagrass decomposition by deploying litterbags in three distinct pH zones (i.e., ambient, low, extreme low pH), which differed in the mean and variability of seawater pH. We replicated the study in two discrete vents for 117 days (litterbags sampled on day 5, 10, 28, 55, and 117). Acidification reduced seagrass detritivore richness and diversity through the loss of less abundant, pH‐sensitive species but increased the abundance of the dominant detritivore (amphipod Gammarella fucicola ). Such compensatory shifts in species abundance caused more than a threefold increase in the total detritivore abundance in lower pH zones. These community changes were associated with increased consumption (52%–112%) and decay of seagrass detritus (up to 67% faster decomposition rate for the slow‐decaying, refractory detrital pool) under acidification. Seagrass detritus deployed in acidified zones showed increased N content and decreased C:N ratio, indicating that altered microbial activities under OA may have affected the decay process. The findings suggest that OA could restructure consumer assemblages and modify plant decomposition in blue carbon ecosystems, which may have important implications for carbon sequestration, nutrient recycling, and trophic transfer. Our study highlights the importance of within‐community response variability and compensatory processes in modulating ecosystem functions under extreme global change scenarios.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

MASTREE+: Time‐series of plant reproductive effort from six continents - Andrew Hacket‐Pain; Jessie J. Foest; Ian S. Pearse; Jalene M. LaMontagne; Walter D. Koenig; Giorgio Vacchiano; Michał Bogdziewicz; Thomas Caignard; Paulina Celebias; Joep van Dormolen; Marcos Fernández‐Martínez; Jose V. Moris; et al. (Global Change Biology, 2022)
Significant gaps remain in understanding the response of plant reproduction to environmental change. This is partly because measuring reproduction in long‐lived plants requires direct observation over many years and such datasets have rarely been made publicly available. Here we introduce MASTREE+, a data set that collates reproductive time‐series data from across the globe and makes these data freely available to the community. MASTREE+ includes 73,828 georeferenced observations of annual reproduction (e.g. seed and fruit counts) in perennial plant populations worldwide. These observations consist of 5971 population‐level time‐series from 974 species in 66 countries. The mean and median time‐series length is 12.4 and 10 years respectively, and the data set includes 1122 series that extend over at least two decades (≥20 years of observations). For a subset of well‐studied species, MASTREE+ includes extensive replication of time‐series across geographical and climatic gradients. Here we describe the open‐access data set, available as a.csv file, and we introduce an associated web‐based app for data exploration. MASTREE+ will provide the basis for improved understanding of the response of long‐lived plant reproduction to environmental change. Additionally, MASTREE+ will enable investigation of the ecology and evolution of reproductive strategies in perennial plants, and the role of plant reproduction as a driver of ecosystem dynamics.

Chemistry of surface water, precipitation, throughfall, leaves, sediment, soil, and air near a gold mining region in P eru - Jacqueline R. Gerson; Natalie Szponar; Arianna Agostini; Rand Alotaibi; Bridget Bergquist; Arabella Chen; Luis E. Fernandez; Kelsey N. Lansdale; Anne H. Lee; Maria F. Machicao; Melissa J. Marchese; Simon N. Topp; et al. (Ecology, 2022)
Artisanal and small‐scale gold mining (ASGM) is the primary global source of anthropogenic mercury (Hg) emissions and a large source of landscape change. ASGM occurs throughout the world, including in the Peruvian Amazon. This data set contains measurements of surface water, precipitation, throughfall, leaves, sediment, soil, and air samples from across the Madre de Dios region of Peru, in locations near and remote from ASGM. These data were collected to determine the fate and transport of Hg across the landscape. Samples were collected in 2018 and 2019. Data predominantly included total Hg and methyl Hg concentrations in surface water, precipitation, throughfall, leaves, sediment, soil, and air. Additional water and soil parameters were also measured to better characterize their chemistry. There are no copyright restrictions; please cite this data paper when the data are used in publication.

Using knowledge to care for country: Indigenous-led evaluations of research to adaptively co-manage Kakadu National Park, Australia - Cathy J. Robinson; Jennifer Mairi Macdonald; Michael Douglas; Justin Perry; Samantha Setterfield; Dennis Cooper; Maria Lee; Jonathan Nadji; Sean Nadji; Alfred Nayinggul; Anita Nayinggul; Kenneth Mangiru; et al. (Sustainability Science, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The pericardium of Oikopleura dioica (Tunicata, Appendicularia) contains two distinct cell types and is rotated by 90 degrees to the left - Mai-Lee Van Le; Maria Novosolov; Dorothee Huchon; Thomas Stach (Zoomorphology, 2021)
The planktonic Oikopleura dioica belongs to Tunicata, the probable sister taxon to Craniota, and might show plesiomorphic characters, conserved from the common lineage of Tunicata and Craniota. In O. dioica a pericardium in a position similar to other chordates but also to the heart and pericardium of craniates is found. Surprisingly, little is known about the ultrastructure of the pericardium in O. dioica . Here, we show based on electron microscopy that the pericardium is completely lined by a single layer of 16 epithelial cells: 6 epithelial myocardial cells on the left side of the pericardium and 10 peritoneal cells constituting the right side. One of the peritoneal cells, situated at the ventral border between peritoneal cells and myocardial cells has an extension that anchors the pericardium to the basal lamina beneath the latero-ventral epidermis. The primary body cavity of O. dioica appears quite uniformly clear in electron microscopic aspect but several sheets, resembling the basal lamina of the pericardium cross the larger spaces of the body cavity and connect to the pericardial basal lamina. This is the first detailed description of two distinct cell types in the epithelial lining of the pericardium of O. dioica. In comparison with other chordates, we conclude that two cell types can be reconstructed for the last common ancestor of Chordata at least. The position of the pericardium at the intersection of trunk and tail in combination with the basal-lamina like sheets spanning the hemocoel is probably of importance for the function of the circulation of the hemocoelic fluid. Similar to the tail, the axis of the pericardium is shifted through 90 degrees to the left as compared to the main body axis of the trunk and we infer that this shift is an apomorphic character of Appendicularia.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Neurological diseases and COVID-19: prospective analyses using the UK Biobank - Nicola Veronese; Lee Smith; Mario Barbagallo; Gianluigi Giannelli; Maria Gabriella Caruso; Anna Maria Cisternino; Maria Notarnicola; Chao Cao; Thomas Waldhoer; Lin Yang (Acta Neurologica Belgica, 2021)
COVID-19 (Coronavirus disease-19) may present with neurological signs, but whether people already affected by neurological conditions are at a higher risk of contracting COVID-19 is still not known. We, therefore, aimed to investigate the association of previously diagnosed neurological conditions with COVID-19. 502,536 community-dwelling UK Biobank participants (54.4% male, mean age 56.6 ± 10.3 years) were included. Among these, 57,463 participants had a diagnosis of neurological conditions (11.43%) and a total of 1326 COVID-19-positive cases were identified (0.26%). Neurological conditions were identified through medical history and linkage to data on hospital admissions (ICD-10 code G00–G99). COVID-19 presence was diagnosed using the data provided by Public Health England. The association of previous diagnosis of neurological conditions with COVID-19 was evaluated through logistic regressions, adjusted for potential confounders, reported as odds ratios (ORs) with their 95% confidence intervals (CIs). Nerve, nerve root and plexus disorders (G50–G59) were the most common conditions identified. The presence of COVID-19 was almost doubled in neurological conditions compared to the general population (0.45 vs. 0.24%, p

A linked geomorphological and geophysical modelling methodology applied to an active landslide - Jimmy Boyd; Jonathan Chambers; Paul Wilkinson; Maria Peppa; Arnaud Watlet; Matt Kirkham; Lee Jones; Russel Swift; Phil Meldrum; Sebastian Uhlemann; Andrew Binley (Landslides, 2021)
Moisture-induced landslides are a global geohazard; mitigating the risk posed by landslides requires an understanding of the hydrological and geological conditions present within a given slope. Recently, numerous geophysical studies have been attempted to characterise slow-moving landslides, with an emphasis on developing geoelectrical methods as a hydrological monitoring tool. However, landslides pose specific challenges for processing geoelectrical data in long-term monitoring contexts as the sensor arrays can move with slope movements. Here we present an approach for processing long-term (over 8 years) geoelectrical monitoring data from an active slow-moving landslide, Hollin Hill, situated in Lias rocks in the southern Howardian Hills, UK. These slope movements distorted the initial setup of the monitoring array and need to be incorporated into a time-lapse resistivity processing workflow to avoid imaging artefacts. We retrospectively sourced seven digital terrain models to inform the topography of our imaging volumes, which were acquired by either Unmanned Aerial Vehicle (UAV)-based photogrammetry or terrestrial laser ranging systems. An irregular grid of wooden pegs was periodically surveyed with a global position system, from which distortions to the terrain model and electrode positions can be modelled with thin plate splines. In order to effectively model the time-series electrical resistivity images, a baseline constraint is applied within the inversion scheme; the result of the study is a time-lapse series of resistivity volumes which also incorporate slope movements. The workflow presented here should be adaptable for other studies focussed on geophysical/geotechnical monitoring of unstable slopes.

Stable Isotopes Clearly Track Mangrove Inputs and Food Web Changes Along a Reforestation Gradient - Amy Yee-Hui Then; Maria Fernanda Adame; Brian Fry; Ving Ching Chong; Philip M. Riekenberg; Rozainah Mohammad Zakaria; Shing Yip Lee (Ecosystems, 2021)

Current and future trophic interactions in tropical shallow-reef lagoon habitats - Kennedy Wolfe; Dione J. Deaker; Alexia Graba-Landry; Curtis Champion; Sophie Dove; Raymond Lee; Maria Byrne (Coral Reefs, 2021)

Inpainting as a Technique for Estimation of Missing Voxels in Brain Imaging - Angel Torrado-Carvajal; Daniel S. Albrecht; Jeungchan Lee; Ovidiu C. Andronesi; Eva-Maria Ratai; Vitaly Napadow; Marco L. Loggia (Annals of Biomedical Engineering, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Molecular Detection and Assessment of Risk Factors for Tick-Borne Diseases in Sheep and Goats from Turkey - Byamukama Benedicto; Onur Ceylan; Paul Frank Adjou Moumouni; Seung-Hun Lee; Maria Agnes Tumwebaze; Jixu Li; Eloiza May Galon; Mingming Liu; Yongchang Li; Shengwei Ji; Aaron Ringo; Mohamed Rizk; et al. (Acta Parasitologica, 2020)

P2X4 Receptors on Muscle Macrophages Are Required for Development of Hyperalgesia in an Animal Model of Activity-Induced Muscle Pain - Maria Claudia Oliveira-Fusaro; Nicholas S. Gregory; Sandra J. Kolker; Lynn Rasmussen; Lee-Ann H. Allen; Kathleen A. Sluka (Molecular Neurobiology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Diversity of clonal types of Klebsiella pneumoniae causing infections in intensive care neonatal patients in a large urban setting - Livia Helena Justo-da-Silva; Andrea Nunes De-Azeredo; Arnaldo Costa Bueno; Lara Feital Montezzi; Maria Beatriz Gerardin Poirot Leobons; Maria Silvana Alves; Patrícia de Souza Inhaquite; Rosana Rangel Santos; Valéria Brígido Carvalho Girão; Antônio José Ledo Alves da Cunha; Carmem Lucia Pessoa-Silva; Renata Cristina Picão; et al. (Brazilian Journal of Microbiology, 2019)

Adequacy of the Ocean Observation System for Quantifying Regional Heat and Freshwater Storage and Change - Matthew D. Palmer; Paul J. Durack; Maria Paz Chidichimo; John A. Church; Sophie Cravatte; Katy Hill; Johnny A. Johannessen; Johannes Karstensen; Tong Lee; David Legler; Matt Mazloff; Eitarou Oka; et al. (Frontiers in Marine Science, 2019)

Ocean Observations to Improve Our Understanding, Modeling, and Forecasting of Subseasonal-to-Seasonal Variability - Aneesh C. Subramanian; Magdalena A. Balmaseda; Luca Centurioni; Rajib Chattopadhyay; Bruce D. Cornuelle; Charlotte DeMott; Maria Flatau; Yosuke Fujii; Donata Giglio; Sarah T. Gille; Thomas M. Hamill; Harry Hendon; et al. (Frontiers in Marine Science, 2019)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Evolving the Physical Global Ocean Observing System for Research and Application Services Through International Coordination - Bernadette M. Sloyan; John Wilkin; Katherine Louise Hill; Maria Paz Chidichimo; Meghan F. Cronin; Johnny A. Johannessen; Johannes Karstensen; Marjolaine Krug; Tong Lee; Eitarou Oka; Matthew D. Palmer; Benjamin Rabe; et al. (Frontiers in Marine Science, 2019)

Improving engraftment of hepatocyte transplantation using alpha-1 antitrypsin as an immune modulator - Charlotte Lee; Anil Dhawan; Valeria Iansante; Celine Filippi; Ragai Mitry; Joanne Tang; Simon Walker; Raquel Fernandez DaCosta; Siddharth Sinha; Robin D. Hughes; Maria Koulmanda; Emer Fitzpatrick (Journal of Molecular Medicine, 2019)

Collections of Mungbean [Vigna radiata) (L.) R. Wilczek] and urdbean [V. mungo (L.) Hepper] in Vavilov Institute (VIR): traits diversity and trends in the breeding process over the last 100 years - Marina Burlyaeva; Margarita Vishnyakova; Maria Gurkina; Konstanin Kozlov; Cheng-Ruei Lee; Chau-Ti Ting; Roland Schafleitner; Sergey Nuzhdin; Maria Samsonova; Eric von Wettberg (Genetic Resources and Crop Evolution, 2019)

Regionalization and Dynamic Parameterization of Quantum Yield of Photosynthesis to Improve the Ocean Primary Production Estimates From Remote Sensing - Maria Laura Zoffoli; Zhongping Lee; John F. Marra (Frontiers in Marine Science, 2018)

Genetic ablation of adenosine receptor A3 results in articular cartilage degeneration - Ruzanna Shkhyan; Siyoung Lee; Francesca Gullo; Lei Li; Maria Peleli; Mattias Carlstrom; Andrei S. Chagin; Nicholas W. Banks; Sean Limfat; Nancy Q. Liu; Denis Evseenko (Journal of Molecular Medicine, 2018)

Reproductive biology of the tiger pleco Panaqolus tankei (Loricariidae) in a lentic system of the Amazon Basin - Yanne A. Mendes; James T. Lee; Ivana K.S. Viana; Rossineide M. Rocha; Maria A.P. Ferreira (Journal of Fish Biology, 2018)
This study presents the first information on the reproduction of the recently described tiger pleco Panaqolus tankei, from Lake Bolonha in the north‐eastern Amazon Basin. This loricariid has a long reproductive period, fractionated spawning and low fecundity (on average, female gonads contained 37 oocytes), a total length ( L T ) at first maturity of 47.4 mm for females and 54.1 mm L T for males. Correlation of the condition factor and gonado‐somatic index with environmental variables suggests that turbidity favours P. tankei reproduction in this environment.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Response to “Resilience of harbor porpoises to anthropogenic disturbance: Must they really feed continuously?” - Danuta Maria Wisniewska; Mark Johnson; Jonas Teilmann; Laia Rojano‐Doñate; Jeanne Shearer; Signe Sveegaard; Lee A. Miller; Ursula Siebert; Peter Teglberg Madsen (Marine Mammal Science, 2018)

The Eurasian hot nightlife: Environmental forces associated with nocturnality in lizards - Enav Vidan; Uri Roll; Aaron Bauer; Lee Grismer; Peng Guo; Erez Maza; Maria Novosolov; Roberto Sindaco; Philipp Wagner; Jonathan Belmaker; Shai Meiri (Global Ecology and Biogeography, 2017)
Aim Lizards are ancestrally diurnal, and most of them remain so. Nocturnality is common among lizards, but the environmental factors associated with lizard nocturnal activity are still unknown. Here, we contrasted the ambient temperature and productivity hypotheses, where we predicted that cold temperatures will pose a stonger limit to nocturnal species richness than diurnal lizards. Moreover, we contrasted the relative importance of annual, day and night mean temperatures to pinpoint the drivers of nocturnal lizard richness. Location Mainland Eurasia. Methods We collected distribution range and activity time data for all 1,113 lizard species found throughout mainland Eurasia. This represents the largest geographical scope to date, for studies of lizard species richness. We examined the spatial patterns of nocturnal species richness in relationship to diurnal species richness across environmental gradients of ambient temperature and productivity. Results Nocturnal lizards are richest in the tropics and in deserts, and their richness decreases with latitude. However, nocturnal lizards are absent from the highest latitudes and coldest regions inhabited by lizards. Diurnal and nocturnal lizards respond in a similar manner to climatic factors. Ambient temperature has a strong influence on both, whereas productivity is more tightly related to the proportion of nocturnal species. Main conclusions Nocturnality is widespread among Eurasian lizards. However, nocturnal lizards are absent from invariably cold regions, and low temperatures seem to be a limiting factor for lizard activity period. We suggest that the year‐round warm nights of the tropics reduce the cost of being active at night and open the nocturnal niche for many lizards. In hot deserts, the combination of hot days and aridity increases the cost of diurnal activity, whereas nocturnal activity provides a shelter from these extreme conditions.

Organic Agriculture 3.0 is innovation with research - Gerold Rahmann; M. Reza Ardakani; Paolo Bàrberi; Herwart Boehm; Stefano Canali; Mahesh Chander; Wahyudi David; Lucas Dengel; Jan Willem Erisman; Ana C. Galvis-Martinez; Ulrich Hamm; Johannes Kahl; et al. (Organic Agriculture, 2017)

An assessment of air–sea heat fluxes from ocean and coupled reanalyses - Maria Valdivieso; Keith Haines; Magdalena Balmaseda; You-Soon Chang; Marie Drevillon; Nicolas Ferry; Yosuke Fujii; Armin Köhl; Andrea Storto; Takahiro Toyoda; Xiaochun Wang; Jennifer Waters; et al. (Climate Dynamics, 2017)

Interannual-decadal variability of wintertime mixed layer depths in the North Pacific detected by an ensemble of ocean syntheses - Takahiro Toyoda; Yosuke Fujii; Tsurane Kuragano; Naohiro Kosugi; Daisuke Sasano; Masafumi Kamachi; Yoichi Ishikawa; Shuhei Masuda; Kanako Sato; Toshiyuki Awaji; Fabrice Hernandez; Nicolas Ferry; et al. (Climate Dynamics, 2017)

Intercomparison and validation of the mixed layer depth fields of global ocean syntheses - Takahiro Toyoda; Yosuke Fujii; Tsurane Kuragano; Masafumi Kamachi; Yoichi Ishikawa; Shuhei Masuda; Kanako Sato; Toshiyuki Awaji; Fabrice Hernandez; Nicolas Ferry; Stéphanie Guinehut; Matthew J. Martin; et al. (Climate Dynamics, 2017)

Steric sea level variability (1993–2010) in an ensemble of ocean reanalyses and objective analyses - Andrea Storto; Simona Masina; Magdalena Balmaseda; Stéphanie Guinehut; Yan Xue; Tanguy Szekely; Ichiro Fukumori; Gael Forget; You-Soon Chang; Simon A. Good; Armin Köhl; Guillaume Vernieres; et al. (Climate Dynamics, 2017)

Postcollisional cooling history of the Eastern and Southern Alps and its linkage to Adria indentation - Bianca Heberer; Rebecca Lee Reverman; Maria Giuditta Fellin; Franz Neubauer; István Dunkl; Massimiliano Zattin; Diane Seward; Johann Genser; Peter Brack (International Journal of Earth Sciences, 2017)

Genetic diversity patterns in ex situ collections of Oryza officinalis Wall. ex G. Watt revealed by morphological and microsatellite markers - Maria Elizabeth Boncodin Naredo; Sheila Mae Quilloy Mercado; Maria Celeste Naynes Banaticla-Hilario; Myrricar Loren Berdos; Mario Alcantara Rodriguez; Kenneth Lee McNally; Ruaraidh Sackville Hamilton (Genetic Resources and Crop Evolution, 2017)

NKCC1 up-regulation contributes to early post-traumatic seizures and increased post-traumatic seizure susceptibility - Fushun Wang; Xiaowei Wang; Lee A. Shapiro; Maria L. Cotrina; Weimin Liu; Ernest W. Wang; Simeng Gu; Wei Wang; Xiaosheng He; Maiken Nedergaard; Jason H. Huang (Brain Structure and Function, 2017)

Analysis of post-disaster damage and disruptive impacts on the operating status of small businesses after Hurricane Katrina - Sandra Sydnor; Linda Niehm; Yoon Lee; Maria Marshall; Holly Schrank (Natural Hazards, 2017)

Erratum to: Identification of quantitative trait loci for panicle length and yield related traits under different water and P application conditions in tropical region in rice (Oryza sativa L.) - Ian Paul Navea; Maria Stefanie Dwiyanti; Jonghwa Park; Backki Kim; Sangbum Lee; Xing Huang; Hee-Jong Koh; Joong Hyoun Chin (Euphytica, 2017)

Identification of quantitative trait loci for panicle length and yield related traits under different water and P application conditions in tropical region in rice (Oryza sativa L.) - Ian Paul Navea; Maria Stefanie Dwiyanti; Jonghwa Park; Backki Kim; Sangbum Lee; Xing Huang; Hee-Jong Koh; Joong Hyoun Chin (Euphytica, 2017)

In planta cleavage of carotenoids by Arabidopsis carotenoid cleavage dioxygenase 4 in transgenic rice plants - Mi-Hee Song; Sun-Hyung Lim; Jae Kwang Kim; Eun Sung Jung; K. M. Maria John; Min-Kyoung You; Sang-Nag Ahn; Choong Hwan Lee; Sun-Hwa Ha (Plant Biotechnology Reports, 2016)

An overview of food safety and bacterial foodborne zoonoses in food production animals in the Caribbean region - Maria Manuela Mendes Guerra; Andre M. de Almeida; Arve Lee Willingham (Tropical Animal Health and Production, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Acute Response of the Hippocampal Transcriptome Following Mild Traumatic Brain Injury After Controlled Cortical Impact in the Rat - Babru B. Samal; Cameron K. Waites; Camila Almeida-Suhett; Zheng Li; Ann M. Marini; Nihar R. Samal; Abdel Elkahloun; Maria F. M. Braga; Lee E. Eiden (Journal of Molecular Neuroscience, 2015)

The Relationship Between Patterns of Benthic Fauna and Zooplankton in the Chukchi Sea and Physical Forcing - Maria Pisareva; Robert Pickart; Katrin Iken; Elizaveta Ershova; Jacqueline Grebmeier; Lee Cooper; Bodil Bluhm; Carolina Nobre; Russell Hopcroft; Haoguo Hu; Jia Wang; Carin Ashjian; et al. (Oceanography, 2015)

Multimodel ensembles of wheat growth: many models are better than one - Pierre Martre; Daniel Wallach; Senthold Asseng; Frank Ewert; James W. Jones; Reimund P. Rötter; Kenneth J. Boote; Alex C. Ruane; Peter J. Thorburn; Davide Cammarano; Jerry L. Hatfield; Cynthia Rosenzweig; et al. (Global Change Biology, 2015)
Crop models of crop growth are increasingly used to quantify the impact of global changes due to climate or crop management. Therefore, accuracy of simulation results is a major concern. Studies with ensembles of crop models can give valuable information about model accuracy and uncertainty, but such studies are difficult to organize and have only recently begun. We report on the largest ensemble study to date, of 27 wheat models tested in four contrasting locations for their accuracy in simulating multiple crop growth and yield variables. The relative error averaged over models was 24–38% for the different end‐of‐season variables including grain yield ( GY ) and grain protein concentration ( GPC ). There was little relation between error of a model for GY or GPC and error for in‐season variables. Thus, most models did not arrive at accurate simulations of GY and GPC by accurately simulating preceding growth dynamics. Ensemble simulations, taking either the mean (e‐mean) or median (e‐median) of simulated values, gave better estimates than any individual model when all variables were considered. Compared to individual models, e‐median ranked first in simulating measured GY and third in GPC . The error of e‐mean and e‐median declined with an increasing number of ensemble members, with little decrease beyond 10 models. We conclude that multimodel ensembles can be used to create new estimators with improved accuracy and consistency in simulating growth dynamics. We argue that these results are applicable to other crop species, and hypothesize that they apply more generally to ecological system models.

Diet alters probiotic L actobacillus persistence and function in the intestine - Sybille Tachon; Bokyung Lee; Maria L. Marco (Environmental Microbiology, 2014)
Summary We investigated the effects of host diet on the intestinal persistence and gene expression of L actobacillus plantarum WCFS 1 in healthy and health‐compromised, 2,4,6‐trinitrobenzene sulfonic acid ( TNBS )‐treated mice. Mice fed either a low‐fat chow diet ( CD ) or high fat and sucrose Western diet ( WD ) received 10 9 L . plantarum WCFS 1 cells for five consecutive days. L actobacillus plantarum persistence was 10‐ to 100‐fold greater in the intestines of WD ‐fed compared with CD ‐fed mice. TNBS , an intestinal irritant that induces the development of inflammatory bowel disease‐like symptoms, resulted in up to a 10 4 ‐fold increase in L . plantarum survival in the digestive tract relative to healthy animals. Expression levels of 12 metabolic and gut‐inducible L . plantarum genes were differentially affected by diet and TNBS administration. Pyrosequencing of 16 S rRNA transcripts from the indigenous intestinal microbiota showed that WD resulted in significant reductions in proportions of metabolically active indigenous L actobacillus species and increases in the Desulfovibrionaceae family. Feeding L . plantarum WCFS 1 resulted in lower levels of colitis and higher concentrations of colonic IL ‐10 and IL ‐12 in WD and not CD ‐fed mice. Interactions between probiotics, nutritional components and the intestinal bacteria should be considered when examining for probiotic‐mediated effects and elucidating mechanisms of probiotic function in the mammalian gut.

Reliability of HSP70 (HSPA) expression as a prognostic marker in glioma - Glenda Maria Beaman; Sarah R. Dennison; Lee K. Chatfield; David A. Phoenix (Molecular and Cellular Biochemistry, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Multi-Scale Parameterisation of a Myocardial Perfusion Model Using Whole-Organ Arterial Networks - Eoin R. Hyde; Andrew N. Cookson; Jack Lee; Christian Michler; Ayush Goyal; Taha Sochi; Radomir Chabiniok; Matthew Sinclair; David A. Nordsletten; Jos Spaan; Jeroen P. H. M. van den Wijngaard; Maria Siebes; et al. (Annals of Biomedical Engineering, 2014)

Journal Clubs: An Educational Approach to Advance Understanding Among Community Partners and Academic Researchers About CBPR and Cancer Health Disparities - Susan T. Vadaparampil; Vani N. Simmons; Ji-Hyun Lee; Teri Malo; Lynne Klasko; Maria Rodriguez; Rhonda Waddell; Clement K. Gwede; Cathy D. Meade (Journal of Cancer Education, 2014)

Myocardial perfusion distribution and coronary arterial pressure and flow signals: clinical relevance in relation to multiscale modeling, a review - Froukje Nolte; Eoin R. Hyde; Cristina Rolandi; Jack Lee; Pepijn van Horssen; Kal Asrress; Jeroen P. H. M. van den Wijngaard; Andrew N. Cookson; Tim van de Hoef; Radomir Chabiniok; Reza Razavi; Christian Michler; et al. (Medical & Biological Engineering & Computing, 2013)

Abundance of denitrification genes under different peizometer depths in four Irish agricultural groundwater sites - Maria Barrett; Mohammad M. R. Jahangir; Changsoo Lee; Cindy J. Smith; Niamh Bhreathnach; Gavin Collins; Karl G. Richards; Vincent O’Flaherty (Environmental Science and Pollution Research, 2013)

Intrafamilial disclosure of risk for hereditary breast and ovarian cancer: points to consider - Lee Black; Kelly A. McClellan; Denise Avard; Bartha Maria Knoppers (Journal of Community Genetics, 2013)

A comprehensive review of climate adaptation in the United States: more than before, but less than needed - Rosina Bierbaum; Joel B. Smith; Arthur Lee; Maria Blair; Lynne Carter; F. Stuart Chapin; Paul Fleming; Susan Ruffo; Missy Stults; Shannon McNeeley; Emily Wasley; Laura Verduzco (Mitigation and Adaptation Strategies for Global Change, 2013)

EURRECA—Estimating Iron Requirements for Deriving Dietary Reference Values - Linda J. Harvey; Cristiana Berti; Amelie Casgrain; Irene Cetin; Rachel Collings; Mirjana Gurinovic; Maria Hermoso; Lee Hooper; Rachel Hurst; Berthold Koletzko; Joy Ngo; Blanca Roman Viñas; et al. (Critical Reviews in Food Science and Nutrition, 2013)

EURRECA—Estimating Selenium Requirements for Deriving Dietary Reference Values - Rachel Hurst; Rachel Collings; Linda J. Harvey; Maria King; Lee Hooper; Jildau Bouwman; Mirjana Gurinovic; Susan J. Fairweather-Tait (Critical Reviews in Food Science and Nutrition, 2013)

Is body size associated with ovarian cancer in southern Chinese women? - Dada Su; Maria Pasalich; Colin W. Binns; Andy H. Lee (Cancer Causes & Control, 2012)

Relationship between baseline brain metabolism measured using [18F]FDG PET and memory and executive function in prodromal and early Alzheimer’s disease - Christian Habeck; Shannon Risacher; Grace J. Lee; M. Maria Glymour; Elizabeth Mormino; Shubhabrata Mukherjee; Sungeun Kim; Kwangsik Nho; Charles DeCarli; Andrew J. Saykin; Paul K. Crane (Brain Imaging and Behavior, 2012)

Voxel and surface-based topography of memory and executive deficits in mild cognitive impairment and Alzheimer’s disease - Kwangsik Nho; Shannon L. Risacher; Paul K. Crane; Charles DeCarli; M. Maria Glymour; Christian Habeck; Sungeun Kim; Grace J. Lee; Elizabeth Mormino; Shubhabrata Mukherjee; Li Shen; John D. West; et al. (Brain Imaging and Behavior, 2012)

Genetic architecture of resilience of executive functioning - Shubhabrata Mukherjee; Sungeun Kim; Laura E. Gibbons; Kwangsik Nho; Shannon L. Risacher; M. Maria Glymour; Christian Habeck; Grace J. Lee; Elizabeth Mormino; Nilüfer Ertekin-Taner; Thomas J. Montine; Charles DeCarli; et al. (Brain Imaging and Behavior, 2012)

A novel COCH mutation associated with autosomal dominant nonsyndromic hearing loss disrupts the structural stability of the vWFA2 domain - Hyun-Ju Cho; Hong-Joon Park; Maria Trexler; Hanka Venselaar; Kyu-Yup Lee; Nahid G. Robertson; Jeong-In Baek; Beom Sik Kang; Cynthia C. Morton; Gert Vriend; László Patthy; Un-Kyung Kim (Journal of Molecular Medicine, 2012)

Novel, panzootic and hybrid genotypes of amphibian chytridiomycosis associated with the bullfrog trade - LISA M. SCHLOEGEL; LUÍS FELIPE TOLEDO; JOYCE E. LONGCORE; SASHA E. GREENSPAN; CONRADO AUGUSTO VIEIRA; MARIA LEE; SERENA ZHAO; CATHERINE WANGEN; CLAUDIA MARIS FERREIRA; MÁRCIO HIPOLITO; ANGELA J. DAVIES; CHRISTINA A. CUOMO; et al. (Molecular Ecology, 2012)
Global amphibian declines are linked with the presence of specific, highly virulent genotypes of the emerging fungal disease chytridiomycosis caused by Batrachochytrium dendrobatidis ( Bd ) known as the global panzootic lineage ( Bd ‐GPL). The global trade in amphibians for human consumption is suspected to have facilitated emergence of the disease, but evidence to support this is largely lacking. Here, we investigated the role the Lithobates catesbeianus (North American bullfrog) trade in spreading Bd genotypes by comparing strains associated with L. catesbeianus to a global panel using 36 sequenced loci from multiple chromosomal regions. Most bullfrogs were infected with Bd ‐GPL genotypes, but we also detected novel, highly divergent Bd genotypes ( Bd ‐Brazil) from a live bullfrog in a US market and from native Brazilian anurans in the Atlantic Forest where bullfrogs are widely farmed. Sexual reproduction was also detected for the first time in Bd in the form of a hybrid genotype between the Bd‐ GPL and Bd ‐Brazil lineages in the Atlantic Forest. Despite the demonstration that ribosomal RNA types in Bd fail to undergo concerted evolution (over 20 sequence types may be found in a single strain), the Bd‐ GPL and Bd ‐Brazil lineages form largely separate clusters of related internal transcribed spacer (ITS) RNA sequences. Using ITS sequences, we then demonstrate the presence of Bd ‐Brazil in Japan, primarily on invasive L. catesbeianus . The finding that Bd is capable of sexual reproduction between panzootic and endemic genotypes emphasizes the risk of international wildlife trade as a source of additional Bd epizootics owing to hybridization.

Mass spectrometric identification of proteins that interact through specific domains of the poly(A) binding protein - Roy Richardson; Clyde L. Denis; Chongxu Zhang; Maria E. O. Nielsen; Yueh-Chin Chiang; Morten Kierkegaard; Xin Wang; Darren J. Lee; Jens S. Andersen; Gang Yao (Molecular Genetics and Genomics, 2012)

Uptake of copper from plasma proteins in cells where expression of CTR1 has been modulated - Theodros Z. Kidane; Ramin Farhad; Kyoung Jin Lee; Abraham Santos; Eric Russo; Maria C. Linder (BioMetals, 2012)

A Muscle’s Force Depends on the Recruitment Patterns of Its Fibers - James M. Wakeling; Sabrina S. M. Lee; Allison S. Arnold; Maria de Boef Miara; Andrew A. Biewener (Annals of Biomedical Engineering, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Different response of silicate fertilizer having electron acceptors on methane emission in rice paddy soil under green manuring - Chang Hoon Lee; Sang Yoon Kim; Maria B. Villamil; Prabhat Pramanik; Chang Ok Hong; Pil Joo Kim (Biology and Fertility of Soils, 2012)

Behavioral Variant Frontotemporal Dementia with Corticobasal Degeneration Pathology: Phenotypic Comparison to bvFTD with Pick’s Disease - Katherine P. Rankin; Mary Catherine Mayo; William W. Seeley; Suzee Lee; Gil Rabinovici; Maria Luisa Gorno-Tempini; Adam L. Boxer; Michael W. Weiner; John Q. Trojanowski; Stephen J. DeArmond; Bruce L. Miller (Journal of Molecular Neuroscience, 2011)

Removal of arsenate from water by adsorbents: a comparative case study - Sunbaek Bang; Maria E. Pena; Manish Patel; Lee Lippincott; Xiaoguang Meng; Kyoung-Woong Kim (Environmental Geochemistry and Health, 2011)

Anatomic Magnetic Resonance Imaging of the Developing Child and Adolescent Brain and Effects of Genetic Variation - Jay N. Giedd; Michael Stockman; Catherine Weddle; Maria Liverpool; Aaron Alexander-Bloch; Gregory L. Wallace; Nancy R. Lee; Francois Lalonde; Rhoshel K. Lenroot (Neuropsychology Review, 2010)

Genes involved with folate uptake and distribution and their association with colorectal cancer risk - Jane C. Figueiredo; A. Joan Levine; Won H. Lee; David V. Conti; Jenny N. Poynter; Peter T. Campbell; David Duggan; Juan Pablo Lewinger; Maria Elena Martinez; Cornelia M. Ulrich; Polly Newcomb; John Potter; et al. (Cancer Causes & Control, 2010)

Acute and chronic toxicity of atrazine and its metabolites deethylatrazine and deisopropylatrazine on aquatic organisms - Kimberly Ralston-Hooper; Jeff Hardy; Leighanne Hahn; Hugo Ochoa-Acuña; Linda S. Lee; Robert Mollenhauer; Maria S. Sepúlveda (Ecotoxicology, 2009)

Enhancement of the antioxidants ergothioneine and selenium in Pleurotus eryngii var. eryngii basidiomata through cultural practices - Alma E. Rodriguez Estrada; Hyun-Ju Lee; Robert B. Beelman; Maria del Mar Jimenez-Gasco; Daniel J. Royse (World Journal of Microbiology and Biotechnology, 2009)

Occupational paraquat exposure of agricultural workers in large Costa Rican farms - Kiyoung Lee; Eun-Kee Park; Maria Stoecklin-Marois; Marja E. Koivunen; Shirley J. Gee; Bruce D. Hammock; Laurel A. Beckett; Marc B. Schenker (International Archives of Occupational and Environmental Health, 2009)

Structure and function of murine cytomegalovirus MHC-I-like molecules: how the virus turned the host defense to its advantage - Janet Mans; Li Zhi; Maria Jamela R. Revilleza; Lee Smith; Alec Redwood; Kannan Natarajan; David H. Margulies (Immunologic Research, 2009)

Effect of culture conditions on the production of ligninolytic enzymes by white rot fungi Phanerochaete chrysosporium (ATCC 20696) and separation of its lignin peroxidase - Peng Wang; Xiaoke Hu; Sean Cook; Maria Begonia; Ken S. Lee; Huey-Min Hwang (World Journal of Microbiology and Biotechnology, 2008)

Secondary metabolites from Tectona philippinensis - Consolacion Y. Ragasa; Maria Claribel Lapina; Jadz Jevz Lee; Emelina H. Mandia; John A. Rideout (Natural Product Research, 2008)

Cell death in the Purkinje cells of the cerebellum of senescence accelerated mouse (SAMP8) - Yonghong Zhu; Cleo C. L. Lee; W. P. Lam; Maria S. M. Wai; John A. Rudd; David T. Yew (Biogerontology, 2007)

Novel sequence variants in the TMIE gene in families with autosomal recessive nonsyndromic hearing impairment - Regie Lyn P. Santos; Hatem El-Shanti; Shaheen Sikandar; Kwanghyuk Lee; Attya Bhatti; Kai Yan; Maria H. Chahrour; Nathan McArthur; Thanh L. Pham; Amjad Abdullah Mahasneh; Wasim Ahmad; Suzanne M. Leal (Journal of Molecular Medicine, 2006)

Identification and characterization of two related murine genes, Eat2a and Eat2b, encoding single SH2-domain adapters - Silvia Calpe; Erika Erdős; Gongxian Liao; Ninghai Wang; Svend Rietdijk; Maria Simarro; Beata Scholtz; Jill Mooney; Chang Hoon Lee; Min Sun Shin; Éva Rajnavölgyi; John Schatzle; et al. (Immunogenetics, 2006)

A novel autosomal recessive non-syndromic hearing impairment locus (DFNB47) maps to chromosome 2p25.1-p24.3 - Muhammad Jawad Hassan; Regie Lyn P. Santos; Muhammad Arshad Rafiq; Maria H. Chahrour; Thanh L. Pham; Muhammad Wajid; Nadine Hijab; Michael Wambangco; Kwanghyuk Lee; Muhammad Ansar; Kai Yan; Wasim Ahmad; et al. (Human Genetics, 2006)

Influence of Preparation Conditions on Acyclovir-Loaded Poly-d,l-Lactic Acid Nanospheres and Effect of PEG Coating on Ocular Drug Bioavailability - Claudia Giannavola; Claudio Bucolo; Adriana Maltese; Donatella Paolino; Maria Angela Vandelli; Giovanni Puglisi; Vincent H. L. Lee; Massimo Fresta (Pharmaceutical Research, 2003)

Expanding the genetic map of maize with the intermated B73 × Mo17 (IBM) population - Michael Lee; Natalya Sharopova; William D. Beavis; David Grant; Maria Katt; Deborah Blair; Arnel Hallauer (Plant Molecular Biology, 2002)

CRE-decoy oligonucleotide-inhibition of gene expression and tumor growth - Yoon S. Cho-Chung; Yun Gyu Park; Maria Nesterova; Youl Nam Lee; Yee Sook Cho (Molecular and Cellular Biochemistry, 2000)

Improvements in shoot apex regeneration of two fiber crops: cotton and kenaf - Cecilia Zapata; Metinee Srivatanakul; Sung-Hun Park; Byung-Moo Lee; Maria G. Salas; Roberta H. Smith (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Signaling via cAMP in fungi: interconnections with mitogen-activated protein kinase pathways - J. Kronstad; Adriana De Maria; Deanna Funnell; R. David Laidlaw; Nancy Lee; Mário Moniz de Sá; Marilee Ramesh (Archives of Microbiology, 1998)